Role of All India Coordinated Research Project in Development of Floriculture in India - Saha, T. N.; J. Majumder; Kadam, G. B.; Kumar, G.; Tiwari, A. K.; Girish, K. S.; Kumar, R. (International Journal of Bio-resource and Stress Management, 2014)
India, the land of flowers is clearly depicted from the ancient civilization and is intricately associated with right from birth till death. Here, hardly any function is complete without flowers. However commercial floriculture is of recent origin. India’s varied agro-climate, ample sunshine and proximity to the markets of Middle-East and South Asian countries offer great opportunities to harness potential in floriculture and ornamentals. The systematic research in floriculture started with the establishment of All India Coordinated Research Project (AICRP) on Floriculture during 1970-71 by linking the ICAR Institutes with the State Agricultural Universities (SAU’s) to carryout nation-wide interdisciplinary research. The AICRP on Floriculture has a mandate to coordinate floricultural research on genetic resource utilization, crop improvement, standardization of production technology, focus on resource utilization such as productive use of water, developing repository of data bank, plant architecture engineering and management, generating the need-based technology for crop protection and value addition. It also aims at development of environment-friendly, cost-effective and user friendly technologies apt for variable agro-climatic conditions, thereby reducing the dependence on cost-intensive extraneous technologies. At present the AICRP on Floriculture with its 22 coordinated centres (16 Budgetary, 4 institutional and 2 voluntary) are working on 13 ornamental crops viz. Rose, Gladiolus, carnation, Chrysanthemum, marigold, orchid, anthurium, tuberose, Gerbera, lilium, alstroemeria, tulip and daffodils consisting of 68 different research projects focusing on development of new and improved varieties, standardization of production technology including improved measures for control of insect pests and diseases and post harvest technologies, extraction of essential oils, flower drying and identification and agro-techniques for unexplored flowers.